Long non‐coding RNAs in ocular diseases: new and potential therapeutic targets. (17th April 2019) - Zhang, Lixia; Dong, Yanhan; Wang, Yujie; Gao, Jinning; Lv, Jiayi; Sun, Jingguo; Li, Mengjie; Wang, Meng; Zhao, Zhihong; Wang, Jianxun; Xu, Wenhua
Abstract : Long non‐coding RNAs (lncRNAs) are non‐protein coding transcripts containing more than 200 nucleotides. In the past, lncRNAs were considered as 'transcript noise' or 'pseudogenes' and were thus ignored. However, in recent years, lncRNAs have been proven to regulate gene expression at the epigenetic, transcriptional and translational level, and thereby influence cell proliferation, apoptosis, viability, immune response and oxidative stress. Furthermore, increasing evidence points to their involvement in different diseases, including cancer and heart diseases. Recently, lncRNAs were shown to be differentially expressed in ocular tissues and play a significant role in the pathogenesis of ophthalmological disorders such as glaucoma, corneal diseases, cataract, diabetic retinopathy, proliferative vitreoretinopathy and ocular tumors. In this review, we summarize the classification and mechanisms of known lncRNAs, while detailing their biological functions and roles in ocular diseases. Moreover, we provide a concise review of the clinical relevance of lncRNAs as novel, potential therapeutic targets in the treatment of eye diseases. Abstract : Long non‐coding RNAs (lncRNAs) regulate gene expression at the epigenetic, transcriptional and translational level. In recent years, lncRNAs have been found to be involved in ocular diseases. This review summarizes the classification and mechanisms of known lncRNAs, providing also a concise overview of the biological functions, regulatory mechanisms and clinical significance of lncRNAs in relevant ocular diseases (uveal melanoma, diabetic retinopathy, proliferative vitreoretinopathy, retinoblastoma, glaucoma, corneal disease, cataract).